Data recording and use of data tools for pig health management: perspectives of stakeholders in pig farming - Zhou, Xiao; Knörr, Andrea; Garcia Morante, Beatriz; Correia-Gomes, Carla; Dieste Pérez, Lucia; Segalés, Joaquim; Sibila, Marina; Vilalta, Carles; Burrell, Alison; Tobias, Tijs; Siegrist, Michael; Bearth, Angela (Frontiers in Veterinary Science, 2025)
IntroductionData-driven strategies might combat the spreading of infectious pig disease and improve the early detection of potential pig health problems. The current study aimed to explore individual views on data recording and use of data tools for pig health management by recruiting stakeholders (N = 202) in Spain, Ireland, and the Netherlands.MethodsQuestionnaire focused on current on-farm challenges, current status of data recording on farms, and evaluation of the two mock data tools. Particularly, “benchmarking tool” was designed to visualize individual farm’s pig mortality, targeting the management of infectious respiratory and gastrointestinal diseases; and “early-warning tool” was designed to generate an alarm through monitoring coughs in pigs, targeting the management of infectious respiratory diseases.ResultsResults showed that respiratory and gastrointestinal diseases and aggressive behaviors were the most frequently mentioned health challenge and welfare challenge, respectively. Most of the data was more frequently recorded electronically than on paper. In general, the “benchmarking tool” was perceived as useful for the management of infectious respiratory and gastrointestinal diseases, and the “early-warning tool” was evaluated as useful for the management of infectious respiratory diseases. Several barriers to the perceived usefulness of these two tools were identified, such as the lack of contextual information, inconvenience of data input, limited internet access, reliance on one’s own experience and observation, technical hurdles, and mistrust of information output. The perceived usefulness of both tools was higher among highly educated participants, and those who reported being integrators and positive toward technology for disease control. Female participants and those who came from integrated farms evaluated the “early-warning tool” as more useful compared to their counterparts. The perceived usefulness of the “early-warning tool” was negatively affected by age and work experience, but positively affected by extensiveness of data recording, positive attitude toward technology, and the current use of technology.DiscussionIn summary, participants showed optimistic views on the use of data tools to support their decision-making and management of infectious pig respiratory and gastrointestinal diseases. It is noteworthy that data tools should not only convey the value of data for informed decision-making but also consider stakeholders’ preconditions and needs for data tools.